2017
DOI: 10.11606/issn.2316-9079.v16i2p255-267
|View full text |Cite
|
Sign up to set email alerts
|

Nesting in the lizard Phyllopezus pollicaris (Squamata: Phyllodactylidae) and a phylogenetic perspective on communal nesting in the family

Abstract: Nesting in the lizard Phyllopezus pollicaris (Squamata: Phyllodactylidae) and a phylogenetic perspective on communal nesting in the family. Communal nesting occurs in many reptile species. The hypotheses that explain the evolution of such behaviours are still controversial, but will be better understood as more communal nesting records are a communal nesting record for squamate species in a Cerrado core area. We provide nest photographs and detailed neonate measurements and weight. Nests were found during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, even among other gekkotans that lay rigid-shelled eggs incubation periods are not as long as that observed in G. darwinii (e.g. Domingos et al, 2017;Khannoon & Evans, 2020;Kluge, 1967;Somaweera, 2009), highlighting another interesting trait in the reproductive biology of this species.…”
Section: Discussionmentioning
confidence: 82%
“…However, even among other gekkotans that lay rigid-shelled eggs incubation periods are not as long as that observed in G. darwinii (e.g. Domingos et al, 2017;Khannoon & Evans, 2020;Kluge, 1967;Somaweera, 2009), highlighting another interesting trait in the reproductive biology of this species.…”
Section: Discussionmentioning
confidence: 82%
“…Recorded observations of communal nesting in lizards of different families have increased in neotropical regions, including Teiidae (Magnusson andLima 1984, Filadelfo et al 2013), Dactyloidae (Montgomery et al 2011), Sphaerodactylidae (Oda 2004, Oliveira et al 2014, Carvajal-Ocampo et al 2019, Sales et al 2020), Phyllodactylidae (Vitt 1986, Rigui et al 2004, Ávila and Cunha-Avellar 2005, Cassimiro and Rodrigues 2010, Lima et al 2011, Domingos et al 2017, and Gekkonidae Freire 2010, Bezerra et al 2011). Communal nests have been reported for the gekkonid genus Lygodactylus on the African continent (Greer 1967, Simbotwe 1983, Rodríguez-Prieto et al 2010), but currently no records of this behavior have been reported for South American species.…”
mentioning
confidence: 99%